Ultrasonic Sensor and Arduino-Based Smart Glasses for Visually Assisting the Blind - Bolimera, Ravi; K. Vittapu, Sravan; Sankuru, Ravichand; Nandhini Reddy, Shamakuri; Sravya, Marella; Srinath, Singirala (Journal of Electronic Design Engineering, 2023)
This paper presents a cutting-edge solution to address the challenges faced by the visually impaired in navigation. The proposed ultrasonic glasses employ ultrasonic sensor technology to detect obstacles in the user’s path. Through a compact and user-friendly design, the system provides real-time auditory feedback to enhance the user’s awareness of their surroundings. The study includes the design and development of the ultrasonic glasses, rigorous testing to validate their efficacy, and user feedback analysis. Preliminary results suggest that this wearable technology is more promising in terms of individual independence with visual impairments and high mobility, offering a promising avenue for future assistive devices. The proposed device consists of a power supply, a processing unit, a glasses pair, a centre fixed obstacle detection module and a beeping device that acts as an output. The power for the CPU is provided by the power supply. To the CPU, the output device and the obstacle detection module are connected. In general, an ultrasonic sensor acts as an obstacle detection module, a control module is used as a processing unit and the buzzer acts as an output device. The control signals are sent by the control unit to the ultrasonic sensors to get and process the information about the obstacle and alert the person by sending this information to the buzzer which is an output device. The proposed smart glasses are economical, portable and rigid, consumer-friendly and lightweight.